About Mía Gallegos' decolonial gaze: Brief notes regarding A decolonial gaze on the novel Limón Blues - Solórzano-Castillo, Alejandra (2023)
Mía Gallegos gives us several guidelines to walk the path of reflection on Anacristina Rossi's Limón Blues.  The first is the de/colonial analysis, openly exposed as the driving force of her reflection; the other, which adds to the decolonial gaze, is that of intersectional analysis.   Gallegos weaves together the retrospective analysis of the rationalizations and justifications of the modernity/coloniality binomial and of the dichotomic ramifications of power based on the mental categories of coloniality to show us how they shape the characters in Rossi's novel within the framework of their historical, political, social, identity and gender dimensions. Intersectionality refers, on the other hand, to the macro intertwining of the novels Limón Blues by Rossi and Orlandus, by Virginia Woolf, resulting in an exquisite critical essay written by one of Costa Rica's most important contemporary writers.